Prediction Of College Student Achievement Based on Educational Background Using Decision Tree Methods - Ratih Kumalasari Niswatin; Resty Wulanningrum (Institute of Advanced Engineering and Science, 2016)
College student as a product can be used as a reference to show the success of education. This research will build a system prediction of college student achievement based on educational background using decision tree method.The research will be conducted on students of Informatics Engineering Department, Faculty of Engineering, University of Nusantara PGRI Kediri. The objective of this system is to help the new admissions process in the selection of students is based on the predicted results of student achievement and help the department to classify new students based on educational background. The method used to predict student achievement is the algorithm C4.5 decision tree method using several criteria based on the educational background of students before, they arethe uan mathematical value, the uan Indonesianvalue, theuan English value, the majors in the school, and the average report cards in the school of origin. This system will be made based on the web to be more effective, fast and easy to use. This system will produce predictions of student achievement information on Informatics Engineering